A Self‐Contained, Controlled Hatchery System for Rearing Lake Whitefish Embryos for Experimental Aquaculture. (21st May 2014) - Mitz, Charles; Thome, Christopher; Cybulski, Mary Ellen; Laframboise, Lisa; Somers, Christopher M.; Manzon, Richard G.; Wilson, Joanna Y.; Boreham, Douglas R.
Abstract: A self‐contained, small‐scale research hatchery was constructed in a modified chromatography refrigerator equipped with a filtered and UV‐sterilized water recirculation system. Lake Whitefish Coregonus clupeaformis embryos were raised in conventional upwelling hatching jars, in dishes with a continuous slow "drip feed, " and in a variety of static water incubation systems in petri dishes and multiwell plates. The optimal rearing density for petri dishes was found to be 50 embryos per dish, with weekly water changes. The highest survival in multiwell plates was seen in the 6‐ and 24‐well sizes. Survival rates in most multiwell plates and petri dishes, as well as in the hatching jar incubators, were between 40% and 60%, which is in line with survival rates seen in commercial large‐scale rearing. Overall, these techniques permitted the rearing of large numbers of whitefish in separate batches and under controlled conditions, while greatly reducing space requirements and material costs. Our system is well suited for research and other situations requiring the temperature‐controlled rearing of embryos on a small scale.